Jenna sells apples and pears. If 20 apples and 60 pears re sold every hour, there will be 80 pears when all the apples are sold. If 60 apple

Question

Jenna sells apples and pears. If 20 apples and 60 pears re sold every hour, there will be 80 pears when all the apples are sold. If 60 apples and 20 pears are sold every hour, there will be 400 pears when all the apples are sold. How many pears are there at the stall?

in progress 0
Delwyn 2 weeks 2021-08-29T19:40:48+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-29T19:42:32+00:00

    Answer:

    There are 1,360 pears.

    Step-by-step explanation:

    Suppose that there are P pears and A apples.

    We know that:

    “If 20 apples and 60 pears are sold every hour, there will be 80 pears when all the apples are sold.”

    Suppose that all of these are sold after N hours, then:

    20*N = A

    80*N = P – 80

    We also know that:

    “if 60 apples and 20 pears are sold every hour, there will be 400 pears when all the apples are sold.”

    60*N = A

    20*N = P – 400

    Then we have four equations:

    20*N = A

    80*N = P – 80

    60*N = A

    20*N = P – 400

    From the first one and the second one, we get:

    20*N = A = 20*N = P – 400

    A = P – 400

    Now we have 3 equations:

    80*N = P – 80

    60*N = A

    A = P – 400

    Now we can just replace the third equation into the second one, then we get:

    60*N = A = P – 400

    Now we have two equations:

    80*N = P – 80

    60*N = P – 400

    Now, remember that we want to find the number of pears, so we want to find the value of P.

    To do it, we can take the quotient of the two equations, so we get:

    (80*N)/(60*N) = (P – 80)/(P – 400)

    8/6 = (P – 80)/(P – 400)

    Now we can solve this for P

    (8/6)*(P – 400) = P – 80

    (8/6)*P – (8/6)*400 = P – 80

    (8/6)*P – P = (8/6)*400 – 80

    (2/6)*P = (8/6)*400 – 80

    P = (6/2)*( (8/6)*400 – 80 )

    P = 3*( (8/6)*400 – 80 ) = 1,360

    There are 1,360 pears.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )